Peta Digital Kota Bitung - Ferrouw R.I. Ratu; Sumenge T.G. Kaunang; Arie S.M. Lumenta (Universitas Sam Ratulangi, 2012)
Internet as a medium for exchange of informationglobally continues to grow rapidly. These developments includeaspects of technology in developing Geographic InformationSystem. With the emergence of what is termed as WebGIS, theGeographic Information System based on the Internet thatmakes GIS can be accessed from anywhere. We have alsooccurred changes in the pattern of web-based informationsystems, where users not only as consumers, but can becomeproducers and distributors.This system is a new option for application developersto create a more interactive GIS with various features andfacilities therein. GIS also has become a substitute forConventional maps that have existed since long, so GIS can alsobe referred to as the Digital Map. Digital maps can minimizeshortages Conventional Map fragile and inflexible.Bitung City Digital Map is designed to respond to theneeds of geographic information the community needs of BitungCity. Objects that appear in this system of Government Office,Object Tourism and Public Facilities. This system uses Apacheas the web server and TimeMap as the map server.